Gospodarka ukryta w Polsce i jej znaczenie - Grzegorczyk, Wojciech (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
The article is concerned with the problems of functioning of hidden economy in Poland. It presents and systematizes the causes of development of hidden economy and evaluates its role and significance. The causes of its development originate from the essence of management and planning in socialist economy as well as from the current economic policy. The evaluation of hidden economy is difficult because one has to take into account the fact that often the instruments applied by the State towards economic units encourage or even force them to undertake activity within the sphere of hidden economy. One should also distinguish between the activity which is evidently illegal and undertaken on a mass scale and the side-line activity having the character of help rendered to neighbours or sale of one's own produce. The grey- -sector economic activity undoubtedly lowers the income of the State (tax evasions) and leads to severing official economic ties between the market subjects. It also lowers the productivity of economic subjects in the official sector and encourages their negative innovativeness consisting mostly in looking for ways to get around the law. Despite these negative consequences, hidden economy brings also economic advantages. It fills up gaps in supply provided by official sectors, it diminishes the inflation gap, it gives rise to the foundation of new, well equipped market segments and complements the administrative distribution of goods and raw materials. The consequence of its existence is also the growth in income and level of consumption of people participating in the grey sector. The processes of differentiation of levels of consumption increase. One may conclude that the income from official economy serve to satisfy basic needs, whereas the improvement in level of consumption and the growth in real income of the population is connected with the activity in the grey economy sector. Neutralizing the negative consequences of grey economy with respect to private sector should consist among others in introducing order to the economic law, in limiting the authorities' competences to enforce new laws and in guaranting the stability of principles of private sector operation. As to socialized sectors, the scope of administrative regulation of economic processes should be limited and the financial system of enterprises should be adjusted to the requirements of self- -financing and economic self-dependence. The above steps may, in the long run, result in the integration of many forms of hidden economy with its lawful counterpart. In conditions of radical changes in the economic system, i.e. in view of socialization and privatization of the economy, the significance of hidden economy should also be subject to changes. Some of its forms should disappear or decrease, while others (i.e. tax frauds) may develop rapidly. However, in conditions of the liberalization of economic legislation and the legalization of most of the forms of hidden economy, the continued activity in the grey sector should be subject to financial restrictions.
Hidden economy and its significance